Epidemiological monitoring and genetic variation analysis of pathogens associated with porcine viral diarrhea in southern China from 2021 to 2023 - Zhang, Fanfan; Luo, Yangyang; Lin, Cui; Tan, Meifang; Wan, Peiwei; Xie, Baobao; Xiong, Ligen; Ji, Huayuan (Frontiers in Microbiology, 2024)
Large-scale outbreaks of virus-associated severe diarrhea have occurred in pig populations since 2010. To investigate the prevalence and genetic evolution of the diarrhea-associated viruses responsible for the outbreaks, we tested 1,791 diarrhea samples collected from 213 pig farms in five provinces in southern China between 2021 and 2023. The test results showed that porcine epidemic diarrhea virus (PEDV) was the most frequently detected virus. The prevalence rates ranged from 47.40 to 52.22% in samples and 76.06% (162/213) in pig farms. Porcine rotavirus (PoRV) was the second common virus, with prevalence rates ranging from 25.81 to 50.81% in samples and 72.77%(155/213) in pig farms. Porcine delta coronavirus (PDCoV) was the third common virus, with prevalence rates ranging from 16.33 to 17.48% in samples and 38.50% (82/213) in pig farms. The detection rates of both transmissible gastroenteritis virus (TGEV) and porcine acute diarrheal syndrome coronavirus (SADS-CoV) were very low, less than 1.01% in samples and less than 3.76% in pig farms. In this study, we found SADS-CoV only in piglet diarrhea samples from Jiangxi, Guangdong, and Guangxi provinces in China, with a prevalence rate of 5.16% (11/213) in pig farms. Co-infection with these diarrhea-associated viruses is a common occurrence. The most common co-infections were PEDV and PoRV, with a prevalence rate of 6.64% (119/1,791), followed by PDCoV and PoRV, with a prevalence rate of 4.19% (75/1,791). Phylogenetic analyses showed that PEDV and PEDV variants prevalent in southern China during the past three years clustered into genotype GIIb and recombinant PEDV subtypes. Among the currently endemic PEDV, the most common mutations occurred in the collagenase equivalent (COE) and epitope regions of the spike gene. PoRV strains were mainly dominated by the G9 subtype, followed by the G5, G3 and G4 subtypes. Our results suggest that variant PEDV, PDCoV and PoRV are the main pathogens of swine diarrhea, and singular- or co-infection with pathogenic enteric CoV is common in pig herds in southern China. Therefore, prevention and control of porcine viral diarrhea should be given high attention.